Treatment outcomes of hepatectomy and systemic chemotherapy based on oncological resectability criteria for hepatocellular carcinoma - Shohei Komatsu; Yoshihiko Yano; Nobuaki Ishihara; Masahiro Kido; Hidetoshi Gon; Kenji Fukushima; Takeshi Urade; Hiroaki Yanagimoto; Hirochika Toyama; Takumi Fukumoto (Annals of Gastroenterological Surgery)
Abstract Aim The oncological resectability criteria for hepatocellular carcinoma (HCC) have recently been established (R/BR1/BR2), and validating the outcomes is an urgent issue. This study aimed to analyze the outcomes of hepatectomy and systemic chemotherapy based on the oncological resectability criteria. Methods A total of 931 patients in the hepatectomy group and 273 in the systemic chemotherapy group who received atezolizumab/bevacizumab, lenvatinib, or durvalumab plus tremelimumab were recruited. Results The median survival times (MST) in the hepatectomy group were R, 107.2 mo; BR1, 44.4 mo; and BR2, 18.4 mo (p < 0.0001). The MSTs in the systemic chemotherapy group were R, 16.3 mo; BR1, 24.5 mo; and BR2, 16.1 mo (p = 0.3598). A comparison of survival of patients in the BR2 category revealed no significant difference between the two groups for those with modified albumin‐bilirubin grade 1 + 2a (p = 0.7343) and grade 2b + 3 (p = 0.6589). The BR2 definition comprised three tumor factors, and the MST of patients with only one BR2‐defining factor tended to be better in the hepatectomy group than in the systemic chemotherapy group (22.9 vs 20.2 mo, p = 0.0977). Meanwhile, the MST tended to be better in the systemic chemotherapy group than in the hepatectomy group (16.5 vs 12.6 mo) for those with two to three BR2‐defining factors, although the difference was insignificant (p = 0.4252). Conclusion The oncological resectability criteria for HCC effectively stratified the prognosis after hepatectomy. Treatment outcomes of hepatectomy in patients with two to three BR2‐defining factors are limited, suggesting the need for multidisciplinary treatment.